Theoretical Insights into the Coupled Optoelectronic Analysis of InP truncated nanopyramid/Germanium Ttandem Solar Cells. (1st January 2023) - Agnihotri, Suneet Kumar; Prashant, D.V.; Samajdar, D.P.
Highlights: Optical performance of InP TNP/Ge Tandem Solar Cell (SC) studied using FDTD method. Geometrical optimisation of individual subcells performed to achieve current matching. Doping concentration of each cell is optimised to achieve high efficiency. Analytical modelling is performed to obtain the photovoltaic parameters of Tandem SC. PCE of 26.7% is achieved for InP TNP/Ge multijunction SC. Abstract: The rapid progress in photovoltaic sector is motivating researchers to carry out exhaustive investigation of highly efficient, cost-effective solar cells by lowering active material requirements or employing nanostructured Solar Cells (SCs). The detailed-balancing Shockley-Queisser limit of efficiency for thin-film or nanostructure single-junction p–n junction SC imposes a restriction on the Power Conversion Efficiency ( PCE ) corresponding to a particular material. However, by stacking multiple layers of variable bandgap energy materials, the efficiency of the SC can be enhanced to exceed the Shockley-Queisser limit in a multijunction (tandem) SC. In this article, we have stacked two semiconducting layers of different bandgap energies in series in the form of InP truncated nanopyramid (TNP) as a top subcell (Eg = 1.35 eV) grown over Ge substrate as a bottom subcell (Eg = 0.78 eV) and explored the optoelectronic study of this InP TNP on Ge multijunction (tandem) SC using the Ansys Lumerical software. The height of InP TNP nanostructure and thickness of Ge substrate are optimized to achieve equal current density ( J sc ) in order to fulfill the current matching condition for a tandem SC. J sc of 23.1 mA/cm 2 and 22.9 mA/cm 2 are obtained for InP TNP with height h1 = 1 μm and Ge substrate with height h2 = 700 nm, respectively. For the electrical analysis of the InP TNP and Ge subcells, we have optimized the doping profile of the p-n region of each subcell in order to obtain a similar electrical J sc . Finally, we have obtained the J-V plot of the proposed tandem SC using the mathematical equations for two series connected photovoltaic cells.